The interconnection between different trimesters of pregnancy and the risk of COVID-19 - Shumilina, Tetiana; Tsmur , Olga (The Ukrainian Scientific Medical Youth Journal, 2023)
this article summarizes the issues within the framework of the scientific discussion regarding the interconnection between different trimesters of pregnancy and the risk of COVID-19. The main objective of this study is to assess the impact of the risk of COVID-19 from the time of infection, namely from different trimesters, to understand the risks of complications at different stages of pregnancy, to assess the impact of the trimester of infection with COVID-19 on the progression of the disease, to determine whether the frequency of progression of the disease of COVID-19 increases with increasing gestational age. Through a detailed study of literature sources, systematization and approaches to solving the problem, it was found that the outbreak of the COVID-19 pandemic in the United States resulted in more than 97 million infections and more than 1.06 million deaths. Approximately 182,000 cases were reported among pregnant women, with 285 maternal deaths. Normal pregnancy is mainly associated with a decrease in functional residual lung capacity by 20-30% and an increase in oxygen consumption by 20%. As a result, lower respiratory tract infections are poorly tolerated, especially in the third trimester. The relevance of the study of this pathology lies in the fact that pregnant patients have a higher risk of infection with coronavirus 2 (SARS-CoV-2) in a severe or critical form compared to non-pregnant women of the same age. In addition, this disparity was exacerbated during the Delta variant surge. An increased risk of adverse outcomes for newborns and mothers is associated with a severe course of COVID-19 during pregnancy. However, little is known about the influence of the time of infection during pregnancy on such risks, so it can lead to errors in the treatment of such pregnant women, which prevents timely, correct treatment and prevention. Methods were used in the study of bibliographic and content analysis of the literature, comparative approach and synthesis, as well as semantic grouping regarding the features of the relationship between different trimesters of pregnancy and the risk of COVID-19. All documents found on various official websites were analyzed and the collected information was compared and grouped. The article presents the results of studies that showed that the frequency of progression of the disease of COVID-19 does not differ from the trimester of diagnosis. The disease of moderate, severe or critical degree develops in almost 10% of pregnant women infected with the SARS-CoV-2 virus. These results highlight the importance of preventive measures, including vaccination against COVID-19 before or as early as possible during pregnancy. As vaccination rates among pregnant women increase, further research is needed to understand disease progression. Similarly, disease severity and progression should be further studied in the context of the development of medical therapy and the evolution of new SARS-CoV-2 variants and recurrent infection. Therefore, further research is needed to obtain patient-centered and cost-effectiveness data. The results of this study may be of interest to primary care physicians, gynecologists, and therapists.